Evaluation of polanga (Calophyllum inophyllum) oil cake as a non-conventional ingredient in Labeo rohita (Hamilton, 1822) fingerling feed - Rath, S. C.; Nayak, K. C.; Pradhan, C.; Mohanty, T. K.; Sarkar, S.; Toppo, S.; Mohanta, K. N.; Giri, S. S. (Indian Journal of Fisheries, 2018)
In the present study, polanga (Calophyllum inophyllum) oil cake (POC) was evaluated as a non-conventional ingredient in Labeo rohita (Hamilton, 1822) fingerling feed. Proximate composition and fatty acid analysis of POC indicated that it can be a good source of protein (24.2%) and energy (4.4 kcal g-1). Fatty acid analysis indicated that it is dominated by monoenes (39%) followed by saturates (28.42) and polyunsaturated fatty acids (PUFA) n-6 (27.76%). Further, phenol, tannin and flavonoids were detected as prominent secondary metabolites. Five iso-nitrogenous (25-26%, crude protein) feeds incorporated with POC @ 0% (F1), 10% (F2), 20% (F3), 30% (F4) and 40% (F5) level were fed to L. rohita fingerlings for 90 days in indoor conditions. At the end of the experiment, it was observed that survival percentage (95-97%) of F1, F2 and F3 groups was statistically similar which was significantly higher (p